The Revolving Door and Regulatory Enforcement: Firm-Level Evidence on Tax Rates and IRS Audits - Benjamin C. K. Egerod (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2019)
I argue that by hiring former legislators firms can impact the enforcement of rules. I test the argument with data on firm-level taxes and the IRS's enforcement activities. I compile a database of publicly listed firms, which have hired Members of Congress (MCs) in the period 2004-2015. I show that hiring a former MC decreases the average company's tax rate. The effect is strongest when firms hire the best connected former MCs who served in committees responsible for oversight of the IRS. To investigate whether the effect is driven by selective enforcement, I collect data on IRS audits and find that hiring a former MC is associated with a lower probability of being audited. Additional tests do not suggest that the findings are driven by general rule changes or lobbying activities. This indicates that rules are enforced differently against politically connected firms.
Keywords: 330; Unternehmensbesteuerung; Interessenpolitik; Rechtsdurchsetzung; Finanzverwaltung; Steuerpolitik; USA